Sejarah Rumah Sakit Pada Perkebunan N.V. Deli Maatschappij Di Sumatera Timur (1869—1940) - Junaidi; Budi Agustono; Kiki Maulana Affandi; Muhammad Rasyidin; Asrika Sari Harahap (Badan Riset dan Inovasi Nasional (BRIN), 2026)
This article focused to explain the history of hospitals at N.V. Deli Maatschappij in East Sumatra and their role in maintaining the health of plantation workers during the period 1869–1940. Improvements in health standards were seen among plantation workers, who initially faced dire conditions. As the plantations developed and the need for a sustainable workforce grew, the company invested in health improvements, particularly through the construction of health facilities and infrastructure, such as hospitals, clinics, medical equipment, and the implementation of a health system. This study employs a four-stage historical method: heuristics, source criticism, interpretation, and historiography. The findings indicate that N.V. Deli Maatschappij provided healthcare facilities and services for plantation workers employed by the company. The economic dynamics of the plantation sector in the late 19th century led to a shift in corporate paradigm towards a focus on the future and the sustainability of the plantation industry. As a result, companies sought to improve health standards by strengthening curative measures through the construction of hospitals and healthcare facilities. Throughout its history, there have been three hospitals dedicated to improving the health of plantation workers: the Deli Maatschappij Central Hospital in Medan, the Bangkattan Hospital in Binjai, and the Tanjung Selamat Hospital in Langkat.